Variabilidade espacial de atributos físicos de solos antropogênico e não antropogênico na região de manicoré, AM - Aquino, Renato Eleoterio [UNESP]; Campos, Milton César Costa; de Oliveira, Ivanildo Amorim [UNESP]; Marques Junior, Jose [UNESP]; Silva, Douglas Marcelo Pinheiro; Silva, Diogo André Pinheiro (My University, 2014)
Better knowledge of the anthropogenic soils can help create future scenarios for the Amazon region through information that supports the sustainable planning. The aim of this study was to evaluate the spatial variability of soil physical anthropogenic and not anthropogenic in the region of Manipur, AM. In the study area we selected two, one with no anthropogenic soils (native forest) and another with anthropogenic soils (black earth archaeological). In each area, we established a grid measuring 70 × 70 m and the soils were sampled at the points of intersection of the grid with regular spacing of 10 by 10 feet, making a total of 64 sampling points in each landscape. Soil samples were collected at a depth from 0.0 to 0.10 I did the analyzes physical (texture, bulk density, macroporosity, microporososidade, porosity and aggregate stability). Then, the data were subjected to descriptive statistics and geostatistics. It was found that the anthropogenic and non-anthropogenic soils showed different behaviors in relation ace their spatial structures. The spatial variability that prevailed in anthropogenic and non-anthropogenic soil was moderate and weak indicating that these soils are strongly linked to changes in the soil by extrinsic factors. The soil was observed anthropogenic best results for total porosity, microporosity and bulk density, showing superior characteristics compared for agronomic soil not anthropogenic. And the range of values found in the above two areas were used in the mesh, showing greater spatial continuity in these environments.
Spatial variability of soil physical anthropogenic and non anthropogenic in the region of manicoré, AM
Keywords: Archaeological dark earths; Geostatistics; Soil attributes